Historical dictionary of track and field - Matthews, Peter, 1945- (Historical dictionaries of sports., 2012)
The Historical Dictionary of Track and Field covers the history of this sport through a chronology, an introductory essay, appendixes, and an extensive bibliography. The dictionary section has over 500 cross-referenced entries on key figures, places, competitions, and governing bodies within the sport. This book is an excellent access point for researchers, students, and anyone wanting to know more about the history of track and field.